2010
DOI: 10.1080/21650993.2010.9756087
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Militating Against the Social Inclusion of Low-Income Pakistani Minority Groups in Hong Kong

Abstract: Research findings from an ethnographic study into low-income Pakistani families in Hong Kong indicate the existence of significant barriers in society militating against social inclusion. Racial discrimination contributes to marginalization, reducing life opportunities. Identified problems include educational, linguistic, and employment issues. These factors lead to social exclusion and weakened social capital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Students have diverse learning needs due to their ethnicity, gender, socioeconomic status, preferred learning styles, abilities, and interests (Strand, 2014; Yuen, 2013). Numerous studies have examined the educational attainment of ethnic minority students in K-12 settings (Crabtree & Wong, 2010). In many societies, such as the U.S., the U.K., and Hong Kong SAR, ethnic minority groups are often perceived as underprivileged because they have different educational needs from the dominant group (Crabtree & Wong, 2010; Hue & Kennedy, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Students have diverse learning needs due to their ethnicity, gender, socioeconomic status, preferred learning styles, abilities, and interests (Strand, 2014; Yuen, 2013). Numerous studies have examined the educational attainment of ethnic minority students in K-12 settings (Crabtree & Wong, 2010). In many societies, such as the U.S., the U.K., and Hong Kong SAR, ethnic minority groups are often perceived as underprivileged because they have different educational needs from the dominant group (Crabtree & Wong, 2010; Hue & Kennedy, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have examined the educational attainment of ethnic minority students in K-12 settings (Crabtree & Wong, 2010). In many societies, such as the U.S., the U.K., and Hong Kong SAR, ethnic minority groups are often perceived as underprivileged because they have different educational needs from the dominant group (Crabtree & Wong, 2010; Hue & Kennedy, 2014). In Hong Kong, the academic performance of ethnic minority students is often lower than that of Chinese students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This can create limited life opportunities, such as lower schooling (Kennedy, 2012), and a higher representation of ethnic minorities in low-paying jobs in Hong Kong (Law and Lee, 2014). Ethnic minorities have also frequently reported their struggles in Hong Kong's mainstream society regarding perceived discrimination (Crabtree and Wong, 2013) and social exclusion (Crabtree and Wong, 2010). By incorporating culturally responsive and sensitive social work education and practice, ethnic minorities can be empowered by social workers to overcome these struggles (Crabtree, 2011).…”
Section: The Social Work Profession and Serving Ethnic Minorities In Hong Kongmentioning
confidence: 99%
“…However, they are unable to integrate into Hong Kong society because of language and cultural (negative stereotypes) barriers that deprive them of employment opportunities and access to social services (Crabtree and Wong, forthcoming). Numerous studies have shown that, aside from FDHs, ethnic minorities in Hong Kong face various forms of racial discrimination on a daily basis, including employment (Ku, 2008), housing (Chan and Ku, 2005), education (Loper, 2004), and provision of social services (Crabtree and Wong, 2010).…”
Section: Life Of Hong Kong South and Southeast Asiansmentioning
confidence: 99%